Arguing about causes in law: a semi-formal framework for causal arguments - Adam Wyner (Artificial Intelligence and Law, 2020)
In legal argumentation and liability attribution, disputes over causes play a central role. Legal discussions about causation often have difficulty with cause-in-fact in complex situations, e.g. overdetermination, preemption, omission. We first assess three theories of causation. Then we introduce a semi-formal framework to model causal arguments using both strict and defeasible rules. We apply the framework to the Althen vaccine injury case. Wrapping up the paper, we motivate a causal argumentation framework and propose to integrate current theories of causation.